Quaternion-based AHRS with MEMS Motion Sensor for Biomedical Applications - A. Antunes, R. (2021)
Trabalho apresentado em IEEE IBITeC2021 (International Biomedical Instrumentation and Technology Conference), 20-21 outubro 2021, online